PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KELARUTAN DI KELAS XI MIA SMAN 6 PEKANBARU - Uhkty Fauzyah; Herdini Herdini; Susilawati Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purposes of research are to know the improvement of student learning achievement and the category by implementing problem posing learning model to increased student achievment on the subject of solubility equilibrium in class XI MIA SMAN 6 Pekanbaru.. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The population in the research consist of 4 class, that is XI MIA 1, XI MIA 2, XI MIA 3 and XI MIA 4. The research sample consisted two class, class XI MIA 1 as experiment class and class XI MIA 2 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using test-t right side and N-gain test to choiced the improvement category of student achievement. Research result shown that the implementation of problem posing learning model can improve student learning achievement on the solubility equilibrium subject where tarithmetic = 2,53 > ttable = 1,67 and category increase students achievement in the experimental class at 0,79 with high categories.Keywords : Learning Model Problem Posing, Learning Achievement, Solubility Equilibrium